The effect of reminiscence therapy on quality of life, attitudes to ageing, and depressive symptoms in institutionalized elderly adults with cognitive impairment: A quasi-experimental study - Siverová, Jarmila; Bužgová, Radka (International journal of mental health nursing, 2018)
The aim of this study was to analyse the effect of group narrative reminiscence therapy on cognition, quality of life, attitudes towards ageing, and depressive symptoms in a group of older adults with cognitive impairment in institutional care. A quasi-experimental pretest/post-test control group design was employed. Interventions involving reminiscence therapy with a narrative approach were included in the care plan and implemented in groups of between five and ten respondents once a week for 8 weeks (total 59 participants). The members of the control group (n = 57) received standard care. A study questionnaire was designed to measure demographic characteristics, quality of life (WOHQOL-BREF, WHOQOL-OLD), depressive symptoms (GDS), cognition (MMSE), and attitudes towards ageing (AAQ). Reminiscence therapy positively affected older adults' quality of life (mostly the areas of mental health and social participation), and also their attitudes to ageing and old age. It reduced symptoms of depression, but had no discernible effect on cognitive function. Reminiscence therapy can positively affect selected aspects of quality of life, attitudes towards old age, and symptoms of depression in the elderly in long-term healthcare facilities. Group reminiscence therapy can be used as a nursing intervention.
Keywords: Cognitive Dysfunction; quality of life; lidé; Middle Aged; long-term health care; Attitude to Health; stárnutí; institucionalizace; psychiatrické posuzovací škály; neuropsychologické testy; Female; deprese; Institutionalization; narativní terapie; Quality of Life; dementia; Humans; Neuropsychological Tests; Narrative Therapy; lidé středního věku; reminiscence therapy; mužské pohlaví; Psychotherapy, Group; Depression; ženské pohlaví; Aging; Aged, 80 and over; senioři nad 80 let; kvalita života; Aged; Male; postoj ke zdraví; kognitivní dysfunkce; skupinová psychoterapie; Psychiatric Status Rating Scales; senioři